Kedudukan Majelis Penyelesaian Perselisihan Medis Dalam Undang - Undang Nomor 17 Tahun 2023 Tentang Kesehatan Perspektif Tujuan Hukum Gustav Radbruch - Muhammad Muzakky Zain Ali; Noenik Soekorini; Syahrul Borman (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Law Number 17 of 2023 concerning Health brings significant changes in the handling of medical professional errors in Indonesia. This research aims to analyze the mechanism for the formation and authority of the Medical Dispute Settlement Council as well as the role of the state in Gustav Radbruch's legal perspective. The research method used is a normative juridical approach with descriptive analysis. The research results show that this law integrates various previous regulations, establishing a permanent or ad hoc assembly to uphold ethical standards and professionalism for health workers. The Assembly is tasked with handling complaints and alleged disciplinary violations before they enter the realm of criminal law, offering fairer and more efficient dispute resolution through a restorative and non-litigation approach. The role of the state is very important to guarantee justice, legal certainty and benefits, ensure that the assembly operates fairly and transparently, and provides fair legal protection for patients and medical personnel.